The Peran Guru Pendidikan Agama Islam dalam Menangani Dampak Penggunaan Handphone terhadap Moral dan Akhlak Siswa di SMP Negeri 2 Megaluh - Rida Nova Marinda; Emi Lilawati; Aliyul Wafa (ALSYS, 2026)
Although mobile phones provide various benefits in supporting the learning process, their uncontrolled use has the potential to affect students’ moral and character development. Previous studies have mostly discussed the effects of mobile phone use on student behavior in general, whereas studies specifically analyzing the role of Islamic Religious Education (PAI) teachers in addressing these effects remain limited. This study aimed to analyze the role of PAI teachers in addressing the effects of mobile phone use at SMP Negeri 2 Megaluh, identify its effects on students, and describe the strategies implemented to minimize these effects. The study employed a descriptive qualitative approach with a phenomenological orientation. Data were obtained through observation, interviews, and documentation involving PAI teachers and ninth-grade students. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, while their validity was examined through source, technique, and time triangulation. The findings showed that PAI teachers played a strategic role in shaping students’ morality and character through the cultivation of the values of tarbiyah, ta’lim, and ta’dib, which were integrated into learning, habituation, religious advice, supervision, and collaboration with parents and the school. Excessive mobile phone use negatively affected students’ discipline, responsibility, courtesy, language use, self-control, and social interaction. This study concludes that PAI teachers play an important role in building students’ moral resilience amid the development of digital technology. These findings contribute to the development of Islamic Religious Education studies, particularly regarding the strengthening of students’ morality and character through the integration of religious education, supervision of technology use, and collaboration between schools and parents.